Intensive care nurses' knowledge of evidence based guidelines regarding entotracheal suctioning in an Academic Hospitals in Johannesburg - Ncube, Christine Mmakarabo (My University, 2019)
Background: An evidence-based approach that encompasses current practice, knowledge and observed outcomes in clinical areas is vital for the purpose of delivering best health care practices to patients (Davies, 2008). Purpose: The aim of this study was to determine intensive care nurses’ knowledge for the current evidence-based guidelines of endotracheal suctioning for adult intensive care units at one university-affiliated public hospital in Johannesburg, in order to make recommendations for clinical practice and education of these nurses. Method: A non-experimental, descriptive, quantitative and cross sectional design was utilised in this study. The sample size comprised 80 (n=80) nurses working in adult intensive care units. Data was collected using a structured questionnaire developed by Jordan (2011). The data collection was divided into two sections. The first section was the demographic data, the second section comprised 27 questions and nurse respondents were asked to respond to dichotomous questions and rate their responses (agree/disagree) on a 5-point Likert scale. Data analysis was done by means of descriptive and comparative statistics to meet the study objectives. Statistical tests included Pearson’s correlation (r) and ANOVA tests and Testing was done on the 0.05 (p <0.05) level of significance. Results: The knowledge of intensive care nurses (both trained and non-trained) was found to be average, the mean total score was 63.8% (SD 6.6), which was considered below adequate (cut-off 70%). The study found no statistical (p>0.05) difference in knowledge based on age and years of experience of these nurses. Further, the results of the multivariable linear regression shows that there is no significant (p>0.05) association between qualification (trained and non-trained ICU nurses), years of experience and knowledge. Conclusion: This study concluded that nurses do not have desirable updated knowledge of current evidence based guidelines on ETT suctioning. Concerns were raised about all aspects of endotracheal suctioning and highlighted the need for changes in nursing practice, with clinical guidelines and focused practice-based education.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg in partial fulfilment of the requirements for the degree of Master of Science in Nursing, Johannesburg 2019